Engineering properties and thermal conductivity of lightweight concrete with polyester-coated pumice aggregates - Tuncer Metin; Bideci Alper; Bideci Özlem Sallı; Çomak Bekir; Durmuş Gökhan (Science and Engineering of Composite Materials)
Pumice aggregates stand out with their low density and high porosity. However, their high water retention capacity and low mechanical strength are the primary disadvantages limiting their use in lightweight concrete production. In this study, pumice aggregates with particle sizes ranging from 4 to 16 mm were coated with polyester, known for its superior adhesion and insulation properties, to produce polyester-coated pumice aggregates. Subsequently, five different lightweight concrete mixtures were prepared using 450 kg/m³ cement, incorporating coated and non-coated pumice aggregates as coarse aggregates at replacement ratios of 0, 25, 50, 75, and 100%. Aggregate tests included specific gravity and water absorption, while fresh concretes were evaluated for unit weight and slump. Hardened concretes were tested for dry unit weight, water absorption, ultrasonic pulse velocity (UPV), compressive strength, freeze–thaw resistance, and thermal conductivity. The results revealed that the polyester coating increased the specific gravity of pumice aggregates by up to 45% and reduced water absorption by 85%. The use of coated aggregates increased the unit weight of the concrete but resulted in a reduction in compressive strength and UPV. Despite a compressive strength reduction of up to 58% depending on the coated aggregate content, concrete specimens produced with polyester-coated aggregates exhibited the highest performance in terms of freeze–thaw resistance and thermal conductivity.